Subtropical forest macro-decomposers rapidly transfer litter carbon and nitrogen into soil mineral-associated organic matter - Guoxiang Niu; Tao Liu; Zhen Zhao; Xuebing Zhang; Huiling Guan; Xiaoxiang He; Xiankai Lu (Forest Ecosystems)
Background: Forest soils in tropical and subtropical areas store a significant amount of carbon. Recent frameworks to assess soil organic matter (SOM) dynamics under evolving global conditions suggest that dividing bulk SOM into particulate and mineral-associated organic matter (POM vs. MAOM) is a promising method for identifying how SOM contributes to reducing global warming. Soil macrofauna, earthworms, and millipedes have been found to play an important role in facilitating SOM processes. However, how these two co-existing macrofaunae impact the litter decomposition process and directly impact the formation of POM and MAOM remains unclear. Methods: Here, we set up a microcosm experiment, which consisted of 20 microcosms with four treatments: earthworm and litter addition (E), millipedes and litter addition (M), earthworm, millipedes, and litter addition (E+M), and control (only litter addition) in five replicates. The soil and litter were sterilized prior to beginning the incubation experiment to remove any existing microbes. After incubating the samples for 42 days, the litter properties (mass, C, and N contents), soil physicochemical properties, as well as the C and N contents, and POM and MAOM 13C abundance in the 0–5 and 5–10 ​cm soil layers were measured. Finally, the relative influences of soil physicochemical and microbial properties on the distribution of C and N in the soil fractions were analyzed. Results: The litter mass, C, and N associated with all four treatments significantly decreased after incubation, especially under treatment E+M (litter mass: −58.8%, litter C: −57.0%, litter N: −75.1%, respectively), while earthworm biomass significantly decreased under treatment E. Earthworm or millipede addition alone showed no significant effects on the organic carbon (OC) and total nitrogen (TN) content in the POM fraction, but joint addition of both significantly increased OC and TN regardless of soil depth. Importantly, all three macrofauna treatments increased the OC and TN content and decreased the 13C abundance in the MAOM fraction. More than 65% of the total variations in the distribution of OC and TN throughout the two fractions can be explained by a combination of soil physicochemical and microbial properties. Changes in the OC distribution in the 0–5 ​cm soil layer are likely due to a decrease in soil pH and an increase in arbuscular mycorrhizal fungi (AMF), while those in the 5–10 ​cm layer are probably caused by increases in soil exchangeable Ca and Mg, in addition to fungi and gram-negative (GN) bacteria. The observed TN distribution changes in the 0–5 ​cm soil likely resulted from a decrease in soil pH and increases in AMF, GN, and gram-negative (GP) bacteria, while TN distribution changes in the 5–10 ​cm soil could be explained by increases in exchangeable Mg and GN bacteria. Conclusions: The results indicate that the coexistence of earthworms and millipedes can accelerate the litter decomposition process and store more C in the MAOM fractions. This novel finding helps to unlock the processes by which complex SOM systems serve as C sinks in tropical forests and addresses the importance of soil macrofauna in maintaining C-neutral atmospheric conditions under global climate change.